2021
DOI: 10.3390/polym13173014
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fire Parameters of Polyamide 12 Powder for Additive Technologies

Abstract: The use of additive technologies keeps growing. Increasingly, flammable powder materials are also used in additive technologies, and there is a risk of explosion or fire when using them. The current article deals with the determination of fire parameters of a powder sample of polyamide Sinterit PA12 Smoth in accordance with the EN 14034 and EN ISO/IEC 80079-20-2 standards. For that purpose, a sample at a median size of 27.5 µm and a humidity of 0% wt. was used. The measurements showed that the maximum explosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
2
2
0
Order By: Relevance
“…Advances in Polymer Technology agreement with previous studies [30][31][32][33]. From Figure 6, it is clear that PA shows a peak at a wave number of 3290 cm -1 , related to hydrogen-bonded N-H stretching.…”
Section: Chemical Analysis By Ftirsupporting
confidence: 90%
“…Advances in Polymer Technology agreement with previous studies [30][31][32][33]. From Figure 6, it is clear that PA shows a peak at a wave number of 3290 cm -1 , related to hydrogen-bonded N-H stretching.…”
Section: Chemical Analysis By Ftirsupporting
confidence: 90%
“…No significant differences in the IR spectrum were observed for PA-12 after artificial ageing compared to the non-sterilised state ( Figure 6 and Figure 7 , Table 7 ). A similar effect was observed for samples with ceramic fillers, but there were visible effects of surface modification with nitrogen and silicon compounds, which originate from APTES [ 29 , 30 , 31 ]. Detailed results for these samples are shown in the table ( Table 8 ).…”
Section: Resultssupporting
confidence: 63%
“…The results from the IR measurements are presented below ( Figure 6 , Figure 7 , Figure 8 , Figure 9 and Figure 10 ). The identified characteristic bands are presented in Table 7 and Table 8 for pure PA-12 and samples with ceramic fillers, respectively [ 29 , 30 ]. The IR pattern of pure PA12 before and after artificial ageing are found in Figure 6 and Figure 7 .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the polymer powder PA12 Sinterit utilized in laser sintering was found to be known for exhibiting explosive characteristics. The highest explosion overpressure recorded for the sample was 6.78 bar at a concentration of 750 g•m −3 [20].…”
Section: Polyamide (Pa) 12mentioning
confidence: 95%